EXPLORATION ON THE CONSTRUCTION OF NEW LIBERAL ARTS FOR THE FIRST-CLASS PROGRAM OF BUSINESS ADMINISTRATION IN APPLICATION-ORIENTED UNIVERSITIES: INTEGRATION OF LIBERAL ARTS, BUSINESS, AND ENGINEERING WITH "TECHNOLOGY-ENABLED MANAGEMENT" - Zeng, Pinhong; Yang, Xiaohong (Bhandar: Harvesting Community Service in Asia, 2025)
On November 3, 2020, China officially released the Declaration on the Development of the New Liberal Arts. This Declaration marks a significant strategic step in the “Four New Directions” initiative for higher education in China, which aims to fundamentally transform how the humanities and social sciences are taught and practiced. The development of the New Liberal Arts is firmly rooted in Chinese realities while actively responding to the demands and needs of the modern era. The initiative goes beyond simple curriculum reform, focusing on a comprehensive reconstruction of traditional liberal arts disciplines. The goal is to ensure that humanities education remains relevant, innovative, and capable of producing talents capable of addressing global social, economic, and technological challenges. At the heart of this development lies exploration and practice in several key areas. These include theoretical innovation to develop new frameworks of thinking, value guidance emphasizing values and ethical guidance, cultural heritage to root educational practices in Chinese traditions, and most importantly, interdisciplinary integration. Through interdisciplinary integration, the New Liberal Arts encourages a deeper fusion between the humanities, social sciences, and science, engineering, or technology (STEM), such as integrating Archival Science with Ideological and Political Curriculum thinking. From a New Liberal Arts perspective, the core of this reform is the advancement of a people-centered educational model. This is an effort to redefine the role of education in shaping individuals who are not only educated, but also innovative, insightful, and socially responsible. By prioritizing societal needs and integrating disciplines holistically, the New Liberal Arts Development seeks to create a more dynamic and responsive higher education system, empowering a new generation to become leaders and thinkers in a rapidly changing society.